Interface Engineering of Metal‐Oxide Field‐Effect Transistors for Low‐Drift pH Sensing. Issue 20 (17th September 2021) - Ren, Huihui; Liang, Kun; Li, Dingwei; Zhao, Momo; Li, Fanfan; Wang, Hong; Miao, Xiaohe; Zhou, Taofei; Wen, Liaoyong; Lu, Qiyang; Zhu, Bowen
Abstract: Field‐effect transistors (FETs) with nanoscale channels have emerged as excellent platforms for constructing high‐sensitivity biosensors. However, in typical FET‐based biosensors, the electronic perturbation at channel/electrolyte interfaces results in poor stability and severe signal drifts, making long‐term continuous measurements quite challenging. To address this issue, here the dielectric/semiconductor interface is tailored by depositing an ultrathin layer of Al2 O3 (≈7 nm in thickness) on In2 O3 FETs via solution‐based processes. The results show that the Al2 O3 dielectric layers effectively passivate the In2 O3 channel and endow the device with low operation voltage (0.05 V), high sensitivity (61.9 mV pH −1 ), and low current drift (0.35 mV h −1 ) upon long‐term and continuous pH monitoring. This work paves the way to real‐time biosensing with high sensitivity, excellent stability, and low power consumption. Abstract : Solution‐processed Al2 O3 /In2 O3 dielectric/semiconductor interfaces are achieved for high‐performance field‐effect transistor‐based biosensors (bio‐FETs). The ultrathin Al2 O3 dielectric layer provides effective passivation and insulating effects to In2 O3 channels, enabling bio‐FETs with fast and stable saturation behaviors. The Al2 O3 /In2 O3 ‐based bio‐FETs demonstrate high sensitivity, low drift, and small hysteresis for real‐time, continuous pH sensing.